The energy efficiency rebound effect in general equilibrium - Christoph Böhringer; Nicholas Rivers (University of Oldenburg, Department of Economics, 2018)
We develop a stylized general equilibrium model to decompose the rebound effect of energy efficiency improvements into its partial and general equilibrium components. In our theoretical analysis, we identify key drivers of the general equilibrium rebound effect, including a composition channel, an energy price channel, a labor supply channel, and a growth channel. Based on numerical simulations with both the stylized model as well as a large-scale computable general equilibrium model of the global economy, we show that both general and partial equilibrium components of the rebound effect can be substantial. Our benchmark parameterization suggests a total rebound effect due to an exogenous energy efficiency improvement in the US manufacturing sector of 67% with roughly two-thirds occurring through the partial equilibrium rebound channel and the remaining one-third occurring through the general equilibrium rebound channel.
Keywords: C68; D58; Q43; Q55; 330; energy efficiency; climate change; rebound effect; general equilibrium